Inclusive economic growth in Kenya: The spatial dynamics of poverty - Judith Tyson; Vidya Diwakar; Morakinyo O. Adetutu; James Bishop (Overseas Development Institute (ODI), 2020)
Kenya poses a conundrum. Its top-line economic growth has been impressive and it has been one of the fastest-growing economies in sub-Saharan Africa over the past decade. However, poverty has not fallen as fast as it should have in light of this strong economic growth. Extreme and urban poverty have remained stubbornly high. This report investigates the discrepancy through four dimensions set out in the Swedish International Development Cooperation Agency (SIDA)'s multidimensional poverty framework: economic and social context; environmental risk; politics and institutions; conflict and security. The report finds that poverty and its dynamics are fundamentally related to their multidimensional and interrelated context. It concludes with a discussion of a number of issues that are particularly important to poverty dynamics, which have not been fully incorporated into the SIDA framework, including demographic growth, vulnerability to climate change and the need for political change to tackle corruption.
Keywords: 330; Wirtschaftswachstum; Armutsbekämpfung; Wirkungsanalyse; Kenia